Sonographic Evaluation of Renal Volume and its Correlation with Estimated Glomerular Filtration Rate among Hypertensive Kidney Disease Patients in Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Glomerular filtration rate (GFR) is one of the various indicators used to assess the degree of chronic kidney disease and it is considered the best marker for the estimation of renal function. Ultrasonography has become the standard imaging modality in the investigation of renal diseases due to its noninvasive nature and availability.Aims:This study was aimed at sonographically evaluating renal volume and correlating it with estimated GFR among hypertensive kidney disease patients in Kano, Nigeria.Settings and Design:This was a cross-sectional study conducted among adults with hypertensive kidney disease at Aminu Kano Teaching Hospital (AKTH), Kano, Nigeria from September 2019 to March 2020. A convenient sampling method was employed and included 242 adults with hypertensive kidney disease in a hypertensive group and 242 normotensive participants in a control group.Materials and Methods:Renal dimensions were measured sonographically. The eGFR of each participant was estimated and recorded.Statistical Analysis Used:The data were analyzed using SPSS Inc, USA version 22. The presetPvalue was 0.05.Results:The renal volumes in the hypertensive group were 91.5 ± 29.3 cm3and 103.2 ± 39.6 cm3for right and left kidneys, respectively, while those of normotensive group were 131.43 ± 34.89 cm3and 168.49 ± 45.83 cm3for right and left kidneys, respectively. In the hypertensive group, moderate positive correlations were observed between left kidney volumes and eGFR (r= 0.4;P= 0.001). However, a weak positive correlation was observed between the right kidney volumes and eGFR (r= 0.3;P= 0.001).Conclusion:Renal volume was higher in the control group than in the hypertensive group. There was a moderate positive correlation between the left kidney and eGFR; however, a weak positive correlation was obtained between the right kidney and eGFR.